Synthesis and characterization of pullulan derived hydrogel matrix as carrier for slow release of anti-cancer drug - Bello, Kabiru (International Journal of Advanced Chemistry, 2020)
The present study is aimed at designing a pullulan based hydrogel through grafting technique for slow release of fluorouracil drug. To achieve this, pullulan grafted acrylic acid was synthesized and characterized by FTIR, and FESEM analyses. Swelling was done in different pH solutions with better swelling in pH 2. As such, the drug loading was done in the specified pH environment. The release profile revealed that more than 90 % of the drug could be released within 5 days. The prepared hydrogel may be considered as stimuli responsive materials for oral drug delivery of anti-cancer drugs. Â Â